TENSILE CHARACTERIZATION FOR COTTON AND VELVET - BAYU ARTOMO (NIM: 10210068), TITO
Textile companies still use natural fibers such as cotton as raw material for textiles. But there are also companies which combine natural fibers and synthetic fibers to obtain high-quality fabrics such as velvet. In this study, tensile characteristics of cotton fabrics and velvet fabrics have been tested. The testing were carried out by two methods: using paper holder and without paper holder. The data results are tensile strength, deformation in length, and time of fabrics to fracture. Then, it can be calculated to obtain stress vs strain curves. Then the elastic modulus can be determined from the slope of the initial linear region. Maximum tensile strength and time required to break the fabric also can be determined. The result shows that cotton has a greater ultimate strength than velvet, but velvet is more elastic than cotton.